THE CORRELATIONS BETWEEN LESION LOCATION AND URINARY DISORDERS WITH QUALITY OF LIFE IN ISCHEMIC STROKE PATIENTS AT HASAN SADIKIN HOSPITAL, BANDUNG - Darafiyah, Aini; Tigor, Aaron (Indonesian Urological Association, 2025)
Objective: This study examines quality of life outcomes in post-ischemic stroke patients with urinary disorders at Hasan Sadikin Hospital Bandung in 2023. Material & Methods: This retrospective study analyzed medical registry data from a single center. Quality of life was evaluated using EORTC Core Quality of Life Questionnaire-30 (EORTC QLQ C-30). Descriptive statistics and Chi-Square/Fisher's Exact tests (95% CI, P < 0.005) were used for clinical and demographic data. Multilinear regression tested the relationship between urinary symptom severity and quality of life. Results: The study included 79 ischemic stroke patients in Hasan Sadikin General Hospital. Patients with urinary disorders had an average age of 52 years (SD ± 13.42), mostly within the 50-60 age group. Hypertension was strongly associated with urinary disorders (P < 0.001). Quality of life decline was highest in role and physical function within the functional domain, and fatigue and insomnia within the symptom domain. Age showed no significant relationship with patient quality of life (P = 0.847 and P = 0.804), but a statistically significant link existed between IPSS total score and quality of life functional outcomes in stroke-ischemic patients. Conclusion: A notable link between urinary disorder severity and the functional domain of quality of life was observed. Further investigation into specific quality of life risk factors related to stroke lesion types is recommended. Keywords: Stroke, ischemia, quality of life, urinary disorders.